Measurements of the inclusive neutrino and antineutrino charged current cross sections in MINERvA using the low- ν flux method - Devan J. (2016)
The total cross sections are important ingredients for the current and future neutrino oscillation experiments. We present measurements of the total charged-current neutrino and antineutrino cross sections on scintillator (CH) in the NuMI low-energy beamline using an in situ prediction of the shape of the flux as a function of neutrino energy from 2–50 GeV. This flux prediction takes advantage of the fact that neutrino and antineutrino interactions with low nuclear recoil energy (ν) have a nearly constant cross section as a function of incident neutrino energy. This measurement is the lowest energy application of the low-ν flux technique, the first time it has been used in the NuMI antineutrino beam configuration, and demonstrates that the technique is applicable to future neutrino beams operating at multi-GeVenergies. The cross section measurements presented are the most precise measurements to date below 5 GeV.